Новий район хори Херсонеса елліністичного періоду - Колтухов, С.Г.; Зубар, В.М.; Миц, В.Л. (Археологія, 1992)
Стаття присвячена публікації нових матеріалів, отриманих в ході розвідки в нижній течії р. Альми біля с. Віліно. Статья посвящена публикации результатов археологической разведки, проведенной в 1990 г. в нижнем течении р. Альмы на территории Бахчисарайского района Крымской области, В ходе осмотра памятников в указанном районе было обнаружено античное поселение у с. Вилино, где в конце IV-II вв. до н. э. жили греческие колонисты, тесно связанные с Херсонесом. Во II в. до н. э. жизнь на городище прервалась и возобновилась лишь во II-III вв. Окончательную гибель городища, судя по археологическому материалу, следует относить к III в.
В результате проведенных на городище у с. Вилино работ было установлено, что в конце IV-II вв. до н. э. Херсонесским государством был освоен не только Северо- Западный Крым, но и Западное побережье Таврики, в частности более или менее значительный район в устье р. Альмы. Конечно, в известной мере этот вывод носит предварительный характер, так как только широкие археологические исследования на вновь открытых памятниках могут дать дополнительный материал и подкрепить сделанное заключение более обильными находками. Однако, как представляется, уже сейчас можно говорить о том, что хора Херсонеса по своим размерам была значительно больше, чем это считалось ранее. А это в свою очередь требует известной корректировки в вопросе об экономическом потенциале Херсонесского государства в эллинистический период. The paper is devoted to publication of the results from archaeological prospecting performed in 1990 in the lower current of the river Alma in the territory of the Bakhchisarai district (the Crimean Region). Examination of the relics in this region has revealed an anthic settlement near vil. Vilino, where Greek colonists closely related to the Chersonese lived at the close of the 4th-2nd cent. В. C. In the 2nd cent.B. C. the life in the site of the settlement was broken and then renewed only in the 2nd-3d centuries. Archaeological data show that the final fall of the site of this ancient settlement, should be referred to the 3d century.
The works performed in this settlement near vil. Vilino have permitted determining that at the close of the 4th-2nd cent. В. C. the Chersonese state developed not only the North- Western Crimea but also the Western coast of Tavrika, particularly a more or less significant region in the mouth of the river Alma Certainly, this conclusion is, to a certain extent, a prelim inaiy one, since only wide archaeological research of the anew discovered relics can give additional material and confirm the drawn conclusion by more abundant findings. However, it seems that already nowadays it is possible to dwell on that the dimensions of the Chersonese chora were much larger than it was previously considered. This fact, in its turn, nessecitates certain correction in the problem on economic potential of the Chersonese state in the Hellenistic period.